Effect of Pulsed Electric Fields (PEF) on the ultrastructure and in vitro protein digestibility of bovine longissimus thoracis. (April 2019) - Chian, Feng Ming; Kaur, Lovedeep; Oey, Indrawati; Astruc, Thierry; Hodgkinson, Suzanne; Boland, Michael
Abstract: Pulsed Electric Fields (PEF) has recently been extended to designing appetising and wholesome food products, such as tenderised meat. This process induces structural changes in foods that could affect their digestive properties. The objective of this research was to investigate the effect of PEF on the ultrastructure and in vitro protein digestibility of beef muscle. Two days post-mortem beef longissimus thoracis was PEF-treated using electric field strength of 1.00–1.25 kV/cm at two different pulse numbers of 500 and 2000. The moisture content of the PEF-treated samples was significantly lower ( p  < 0.05) by 1.3%–4.6% than the untreated samples while their pH, colour and protein thermal profile remained unchanged. Transmission electron micrographs showed the weakening of the Z-disk and I-band junctions of PEF-treated samples and their sarcomeres were 25%–38% longer than the control. PEF treatment improved in vitro protein digestibility by at least 18% (up to 31%) and the digestive profiles (SDS-PAGE) of both control and PEF-treated samples were different. This corresponds to more severe Z-disks and I-bands disruption observed in PEF-treated samples after 180 min of simulated digestion, showing that the PEF-treated muscle is more susceptible to enzymatic degradation. Highlights: Low-intensity PEF maintained the pH, colour and protein thermal profile of meat. Moisture loss of meat significantly ( p  < 0.05) increased with rising PEF intensity. PEF caused elongation and physical disruption of sarcomeres. PEF significantly ( p  < 0.05) improved in vitro protein digestibility by ≥ 18%. Severe disruption of Z-disks and I-bands was found in digested PEF-treated meat.